The Effect of E-Zuraidah on Increasing Knowledge and Behavior as Early Detection of Breast Cancer - Zuraidah; Juartika, Wella; Aprilyadi, Nadi; Warijan; Sutarmi (Babali Nursing Research, 2024)
Introduction: Breast cancer is a global health problem and the leading cause of death in women. Therefore, early detection through increased awareness and knowledge about breast cancer and breast cancer screening is essential. Today's teenagers greatly admire and use several social media platforms. For this reason, E-Zuraidah presents information as educational material using two social media platforms, WhatsApp and Instagram. The study objective is to determine the influence of E-Zuraidah on the knowledge and behavior of BSE in the early detection of Breast Cancer. Methods: This study's stages use quasi-experiments with intervention and control groups. The study began with providing education as usual in the classroom, after which it was divided into two groups. Results: One of the groups continued to the WhatsApp and Instagram groups to be re-educated. The results found that the average age of respondents was 15.87 years (SD 0.676), which ranged from 15 years to 18 years, at an average body weight of 47.34 kg (SD 7.447), which ranged from 35 kg to 70 kg, and a height of an average of 155.33 cm (SD 4.912), which ranged from 145-169 cm. The history of cancer in more than half of the respondents was not 58 people (96.7%) compared to other cancers as many as two people (3.3%). In the information experience, more than half of students have received information from 36 people (60%) with education from community health centers, but there are not as many as 24 people (40%). Conclusion: It can be concluded that social media education needs to be done as an approach.